Polymorphism of TNFα with measurement of IL-18, IL-37 and Glutathione in Iraqi patents with Leishmaniasis: Polimorfisme TNFα dengan pengukuran IL-18, IL-37 dan Glutathione dalam paten Irak dengan Leishmaniasis - Aboud, Rabia Ali (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Leishmaniasis remains a significant public health issue, particularly affecting immunocompromised populations and children in endemic regions. Specific Background: The immunopathogenesis involves complex cytokine responses and antioxidant mechanisms, yet limited data exists on the interaction of TNFα polymorphisms and interleukin expression in visceral leishmaniasis. Knowledge Gap: There is a paucity of studies linking genetic variants of TNFα with cytokine profiles and glutathione dynamics in Iraqi patients with L. donovani infections. Aims: This study aimed to assess serum levels of IL-18, IL-37, TNFα, glutathione, and the rs767455 SNP in TNFα among infected individuals. Results: Patients exhibited significantly elevated IL-18, IL-37, TNFα, and IgG levels alongside markedly reduced glutathione compared to controls (P≤0.001). A direct correlation was observed between glutathione and both TNFα (r=0.224, P=0.006) and IL-37 (r=0.155, P=0.05). A SNP variation (AA to GG) in rs767455 was noted in multiple infected individuals. Novelty: This is the first study to report a significant elevation of IL-37 and a defined correlation of glutathione with inflammatory cytokines in visceral leishmaniasis. Implications: These findings underscore the potential of cytokine and glutathione profiling, alongside genetic markers, as diagnostic or prognostic tools in managing leishmaniasis. Highlights: Significant Increase in Cytokines: Patients with visceral leishmaniasis exhibited markedly higher levels of IL-18, IL-37, TNFα, and Glutathione compared to controls. Genetic Variation Identified: A SNP (rs767455) mutation in the TNFα gene was observed in several infected individuals, changing genotype from AA to GG. Correlative Biomarker Insight: Strong correlation found between Glutathione and TNFα/IL-37 levels, suggesting possible biomarker or therapeutic implications. Keywords: Leishmaniasis, TNFα, IL-18, IL-37, Glutathione